(untitled) (Journal of Medical & Health Sciences Review, 2025)
Single Nucleotide Variants (SNVs) are the most common form of sequence alterations found in human genomes, with the potential to influence phenotypic expression and predispose individuals to complex diseases, such as hypertension. One such variant, the missense SNP (rs699) in the AGT gene, results in an amino acid substitution from methionine to threonine, which may lead to elevated blood pressure and increased plasma angiotensinogen (AGT) levels. Although several molecular biology techniques are available for genotyping such variants, many are costly, labour-intensive, and require sophisticated instrumentation. This study aimed to develop a rapid, reliable and cost-effective genotyping protocol for rs699 based on the Tetra-Primer Amplification Refractory Mutation System PCR (Tetra-ARMS PCR) technique. Two sets of primers- comprising two inner and two outer primers- were designed and tested on high-quality DNA extracted from blood samples. A range of PCR conditions was explored, including varying concentrations and ratios of outer to inner primers, different concentrations of PCR reagents and a range of annealing temperatures. The reactions were optimized by systematically adjusting these parameters until consistent and specific amplification of the target genotypes was achieved. The optimized protocol used a 1:3 (0.2:0.6 μM) outer-to-inner primers ratio with an annealing temperature of 61℃. The genotypes were scored by resolving the amplicon on 2% agarose gel, and the resulting genotypes were further validated through Sanger sequencing to ensure accuracy and specificity. In conclusion, a reliable and specific Tetra-ARMS PCR-based genotyping method was successfully developed and optimized for rs699. This protocol will facilitate large-scale case-control studies aimed at investigating the association between rs699 and hypertension.